PERAN EKOSISTEM MANGROVE SEBAGAI PENOPANG KEANEKARAGAMAN HAYATI LAUT DAN KEBERLANJUTAN LINGKUNGAN DI WILAYAH PESISIR DESA SEI NAGA LAWAN, KEC. PERBAUNGAN, SUMATERA UTARA. - Tobing, Rachel Mia (Jurnal Geografi, 2025)
Mangrove ecosystems are one of the most important living systems in coastal areas, especially in Sei Naga Lawan Village. Mangroves function as a transitional area between land and sea, which not only protects the coast from the risk of abrasion and erosion, but also provides crucial shelter for various types of marine life. Using a descriptive qualitative approach to describe the role of mangrove ecosystems in supporting marine biodiversity and their contribution to environmental sustainability, this research collected data through field observations, interviews, and literature review. It is hoped that the results of this research will be able to explain the role of mangrove ecosystems in maintaining marine biodiversity and environmental sustainability in Sei Naga Lawan Village. The purpose of the research is to explain the role of mangrove ecosystems in maintaining marine biodiversity and explain the socio-economic benefits of this mangrove ecosystem. of mangrove ecosystems in maintaining marine biodiversity and explain the socio-economic benefits of this mangrove ecosystem.